1987
DOI: 10.1021/ja00248a031
|View full text |Cite
|
Sign up to set email alerts
|

Crown thioether chemistry: structural and conformational studies of tetrathia-12-crown-4, pentathia-15-crown-5, and hexathia-18-crown-6. Implications for ligand design

Abstract: Both compounds had NMR spectra in CDC13 identical with those of the corresponding pure enantiomers.Mineral Acid Catalyzed Asymmetric Transformations: Synthesis of (R*,S*)-1. A solution of (R*,R*)-1 (2.5 g) in chloroform (100 mL) was treated with a mixture of methanol (5 mL) and hydrochloric acid (5 mL, 10 M). After two weeks, 2.2 g (88% yield) of pure (R*,S*)-1 had separated from the mixture as long colorless needles:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(91 citation statements)
references
References 10 publications
3
87
0
1
Order By: Relevance
“…In [Ni(24s6)l2+, which has all six-membered chelate rings, there are two meridional loops and all others are facial as in our cation. These preferences can be related to ligand dihedral angles that are in turn influenced by intramolecular nonbonding interactions (6 (Fig. 3), the Ni-S lengths and coordination s here bond angles (Table 4) (38).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [Ni(24s6)l2+, which has all six-membered chelate rings, there are two meridional loops and all others are facial as in our cation. These preferences can be related to ligand dihedral angles that are in turn influenced by intramolecular nonbonding interactions (6 (Fig. 3), the Ni-S lengths and coordination s here bond angles (Table 4) (38).…”
Section: Resultsmentioning
confidence: 99%
“…Co-S 2.444(2) C o a 2.098 (6) in [ c o (~o s~) , ]~+ , the "small ring" analogue of L3 (45) (2.320(3), 2.257(3), and 2.395(3) A), which display the expected Jahn-Teller distortion of a low-spin Co(I1) species. In the case of [co(L3)12+, which is high spin (vide infra), such distortion is not apparent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that crown thioethers possess unusual conformation behavior differing from that of oxa-crown ethers, what has important ramifications for coordination chemistry [1]. The title molecule is a new fifteen-membered macrocyclic polydisulfide composed of three repeated 1,3-propanedithiol units connected via three sulfur-sulfur bonds.…”
Section: Discussionmentioning
confidence: 99%
“…The unusual complexation behavior of the tridentate macrocycle 1,4,7-trithiacyclononane (9S3) and related crown thioethers has also been an impetus for this development, and some specific examples of these unexpected properties include their large ligand field strengths [10,11], their ability to reduce electron-electron repulsions and thereby form low spin complexes [12][13][14][15][16][17][18][19], their ability to stabilize unusual oxidation states and coordination geometries [20][21][22][23][24][25][26][27][28] and a rapidly emerging organometallic chemistry [29][30][31][32][33][34]. Several of these thioether macrocycles including 20S6 (1,4,7,11,14,17-Nov-Dec 2001 1281 macrocycles where the exodentate conformation predominates [36][37][38]. The effect highlights the importance of pre-organization in determining the complexation mode of 9S3 and other macrocyclic thioether ligands.…”
Section: Introductionmentioning
confidence: 99%